A light sheet fluorescence microscopy protocol for Caenorhabditis elegans larvae and adults - Smith, Jayson J.; Kenny, Isabel W.; Wolff, Carsten; Cray, Rachel; Kumar, Abhishek; Sherwood, David R.; Matus, David Q. (Frontiers in Cell and Developmental Biology, 2022)
Light sheet fluorescence microscopy (LSFM) has become a method of choice for live imaging because of its fast acquisition and reduced photobleaching and phototoxicity. Despite the strengths and growing availability of LSFM systems, no generalized LSFM mounting protocol has been adapted for live imaging of post-embryonic stages of C. elegans. A major challenge has been to develop methods to limit animal movement using a mounting media that matches the refractive index of the optical system. Here, we describe a simple mounting and immobilization protocol using a refractive-index matched UV-curable hydrogel within fluorinated ethylene propylene (FEP) tubes for efficient and reliable imaging of larval and adult C. elegans stages.